Jouer Frankenstein pour les « speculative eyes » ? l’incidence des premières représentations sur l’énergie rhétorique des fictions scientifiques - Rachel Nisbet (ReS Futurae, 2021)
My contribution to this investigation of science fiction theatre focuses on the early stage adaptations of Frankenstein. Synonymous with unethical scientificity, this narrative is identified as influencing later ’anti-science fiction’ narratives (Stableford 2006, 19). After the publication of Mary Shelley’s novel in 1818, however, theatre adaptations of this text had a much larger audience than the written work for two decades. These performances, Iargely unknown, emphasize the following dyad: scientific invention and the failure of the inventor to promote the positive integration of his creation into society. They present a conflict between the non-verbal rhetorical energy of the man invented by Frankenstein, who is silent in these plays, and the verbal rhetoric of the scientist, who acts as a mediator between his invention and society.